Hubungan Pemakaian Alat Kontrasepsi Dengan Gangguan Siklus Menstruasi Pasangan Usia Subur (PUS) Tahun 2021: The Relationship Between the Use of Contraceptives and Menstrual Cycle Disorders in Couples of Childbearing Age Year 2021 - Mudita Sri Hidayah; Yanti Maryanti (LPPM STIKES Guna Bangsa Yogyakarta, 2023)
Menstrual cycle disorders are often become a problem for couples of childbearing age who use contraceptives, especially hormonal contraceptives namely injectable contraceptives. The problem itself can be in the form of a long cycle or more than 35 days (oligomenorrhea), a short menstrual cycle of less than 21 days (polymenorrhea) and a menstrual absence in 3 months in a row (amenorrhea). This study aims to determine the relationship between the use of contraceptives and menstrual cycle disorders in couples of childbearing age at Puskesmas Piyungan Sub-district, Bantul Yogyakarta in the year of 2021. This study is quantitative analytical study with Cross Sectional approach which was conducted retrospectively. The sampling technique used was Proportional Random Sampling with the total sample of 96 respondents. The analysis used were univariate and bivariate analysis. The results showed that from 58 respondents who used hormonal contraception, 44 respondents (75,9%) experienced abnormal menstrual cycle. Meanwhile, 38 respondents who used non-hormonal contraception at least experienced an abnormal menstrual cycle as many as 6 respondents (15,8%). The Chi-Square test showed that there was a significant relationship between the use of contraceptives and menstrual cycle disorders in couples of childbearing age, namely p = 0,000 < α = 0,05 with OR value of 16,762. There is a significant relationship between the use of contraceptives and menstrual cycle disorders at Puskesmas Piyungan Sub-district, Bantul Yogyakarta.